One-Step Synthesis of Nitrogen-Doped Hydrophilic Mesoporous Carbons from Chitosan-Based Triconstituent System for Drug Release - Wang, Xianshu; Pan, Hongyan; Lin, Qian; Wu, Hong; Jia, Shuangzhu; Shi, Yongyong (Nanoscale research letters, 2019)
In situ nitrogen-doped hydrophilic mesoporous carbon spheres with different carbon-to-silicon (C/Si) ratios (NMCs- x /3, x = 5, 6, 7, and 8) were prepared by one-step method coupled with a spray drying and carbonizing technique, in which triblock copolymer (F127) and tetraethyl orthosilicate (TEOS) were used as template agents, and biocompatible chitosan (CS) was used as the carbon source and nitrogen source. These carbon materials were characterized by TG, BET, XRD, Raman, FTIR, TEM, XPS, and contact angle measuring device. The adsorption and release properties of mesoporous carbon materials for the poorly soluble antitumor drug hydroxycamptothecin (HCPT) were investigated. Results showed that nanospherical mesoporous carbon materials were successfully prepared with high specific surface area (2061.6 m 2 /g), narrowly pore size distribution (2.01–3.65 nm), and high nitrogen content (4.75–6.04%). Those NMCs- x showed a satisfactory hydrophilicity, which gradually increased with the increasing of surface N content. And the better hydrophilicity of NMCs- x was, the larger adsorption capacity for HCPT. The absorption capacity of NMCs- x towards HCPT was in the following orders: q NMCs-5/3 > q NMCs-6/3 > q NMCs-7/3 > q NMCs-8/3 . NMCs-5/3 had the largest saturated adsorption capacity of HCPT (1013.51 mg g −1 ) and higher dissolution rate (93.75%).